2010
DOI: 10.1177/112070001002000305
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage Treatment Protocol for Isolated Septic Acetabular Cup Loosening

Abstract: The aim of this study was to evaluate the treatment of isolated septic acetabular cup loosening without involvement of the prosthesis stem by insertion of an antibiotic-loaded spacer head and stem retention. Between 1999 and 2008, 13 patients (5 men, 8 women, mean age 69 years) were treated according to this regimen. S. epidermidis and S. aureus were the two most commonly identified pathogens. In 12 cases the polymethylmethacrylate spacers were impregnated with 0.5 g gentamicin + 2 g vancomycin per 40 g bone c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…One study combined this procedure along with the use of the vacuum-assisted closure therapy [11] . Two studies reported on partial prosthesis retention [8,13] . In both studies, the infected acetabular cup was removed and an antibiotic-loaded spacer head was placed onto the retained femoral stem.…”
Section: Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…One study combined this procedure along with the use of the vacuum-assisted closure therapy [11] . Two studies reported on partial prosthesis retention [8,13] . In both studies, the infected acetabular cup was removed and an antibiotic-loaded spacer head was placed onto the retained femoral stem.…”
Section: Researchmentioning
confidence: 99%
“…A total of 11 studies reporting on 292 cases could be identified ( Figure 1) [2][3][6][7][8][9][10][11][12][13][14] . Two studies were published before and nine after 2000.…”
Section: Researchmentioning
confidence: 99%
See 3 more Smart Citations